Exploring the potential of curry leaves on mercury‐induced hepatorenal toxicity in an animal model. Issue 2 (13th December 2021) - Ijaz, Muhammad; Arshad, Asma; Awan, Muhammad Ahmad; Tariq, Muhammad Rizwan; Ali, Shinawar Waseem; Ali, Sajid; Shafiq, Muhammad; Ahmed, Saeed; Sheas, Muhammad Naveed; Iftikhar, Madiha; Ahmed, Sheraz; Nasir, Muhammad Adnan; et al.
Abstract: Herbal drugs play an imperative role in healthcare programs in developing countries. Curry leaves have wide medicinal importance and are used to treat various diseases traditionally. The current study was carried out to estimate the extent of mercury toxicity and the potential effect of curry leaves against defined toxicity. The study group comprised 24 rats weighing between 130 and150 g. Group 1 was kept normal, and group 2 was exposed to mercury at 0.4 mg/kg of body weight in the form of mercuric chloride (HgCl2 ). The group 3 animals were treated with curry leaves with a dosage of 300 mg/kg of body weight. Group 4 was treated with curry leaves along with mercury with a dosage of 300 and 0.4 mg/kg consecutively. After 28 days, the rats were killed. Blood sample of all groups were evaluated separately to determine the results of different parameters. The results show that ALP, AST, ALT, urea, bilirubin, and creatinine increased with mercury application and decreased with curry leaf exposure. SOD, CAT, GPx, and GR of the liver as well as the kidney depleted on mercury exposure whereas they increased with curry leaf application. HDL increased with curry leaf application and decreased with mercury treatment, while LDL, triglyceride, and cholesterol decreased with curry leaves and increased with mercury exposure. Organ index in mercury along with curry leaf application got close to normal. Abstract : The extent of mercury toxicity and the potential effect of curry leaves were assessed against the defined toxicity. A total of 24 rats weighing between 130 and 150 g were exposed to mercury and treated with curry leaves for 28 days. Obtained data from this study showed that all the treatments have important effects on liver and kidney parameters, i.e., ALP, AST, ALT and urea, bilirubin, and creatinine increased with mercury application and decreased with curry leaf exposure. SOD, CAT, GPx, and GR of the liver as well as the kidney depleted on mercury exposure whereas increased with curry leaf application.